Performance Evaluation of Graduates Department of Civil Engineering and Planning of Pontianak State Polytechnic - Rika Riyanti; Indah Anjar Reski; Robby Maulidi Arif (Budapest International Research and Critics University, 2022)
The purpose of the study was to evaluate the performance of graduates from the Civil Engineering Department at the Pontianak State Polytechnic to know the assessment of service users from the Civil Engineering and Planning Department graduates on the ability to integrity (ethics and morals), professionalism, foreign language skills, information technology, communication, teamwork, and self-development. Our study method collects field data in interviews, surveys, and observation data. Researchers also use questionnaires distributed to alumni and alumni who use the services of contractors and consultants. The field passed the data research tracer study that determines the extent to which the assessment of alumni and graduate users on the performance of graduates of the Department of Civil Engineering and Planning at the Pontianak State Polytechnic at the same time received advice or input to improve the performance of graduates From the evaluation results above, it is hoped that the data obtained can improve the performance of graduates so that by itself it can increase accreditation for two study programs, namely the D-III Civil Engineering Study Program and the D-IV Housing and Settlement Planning Study Program—learning program and learning program. Thus, we hope that the results of this study will be helpful for all parties; academics, policymakers, and other researchers.